Payroll Taxes, Wealth and Employment in Neoclassical Theory: Neutrality or Non-Neutrality? - HOON, Hian Teck (Institutional Knowledge at Singapore Management University, 2009)
The theoretical proposition that temporarily below-normal tax rates on labor this year, when merged with the prospect of reversion to normal rates next year, will encourage households to squeeze more work into this year and to work less in future years is well-founded. This proposition was recently tested anew on Icelandic data and performed well empirically (Bianchi, Gudmundsson and Zoega (2001)). But would a permanent cut in tax rates on labor encourage more work permanently—with no diminution of effectiveness? Conversely, does a permanent increase in tax rates on labor cause a permanent decline in hours worked?